PENGARUH KECERDASAN EMOSIONAL DAN INNER CHIL TERHADAP FORGIVENESS PADA MAHASISWA YANG MEMILIKI PERSTASI AKADEMIK BAIK (MINIMAL IPS 3,5) - Suciati, Rozakiya Dwi; Mariyati, Lely Ika (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to determine the effect of emotional intelligence and inner child on forgiveness in students who have good academic achievement (at least IPS 3.5). The background of this study is based on the importance of the ability to forgive in maintaining emotional balance, especially in high-achieving students who are prone to experiencing academic and emotional pressure. This study uses a quantitative approach with multiple linear regression methods. The research subjects were 182 active students of Muhammadiyah University of Sidoarjo Psychology study program, selected through purposive sampling technique. Data were collected using three psychological scales, namely the forgiveness scale, emotional intelligence scale, and inner child scale. The results showed that simultaneously, emotional intelligence and inner child had a significant effect on forgiveness (R² = 0.925; p 0.001). However, partially only emotional intelligence has a significant effect on forgiveness (p 0.001), while the inner child does not show a significant effect (p = 0.921). These findings suggest that emotional intelligence is an important factor in improving forgiveness in high-achieving students